Florida Dairy Farm Situation and Outlook 2005 - Russ Giesy; Albert De Vries; Dave Bray; Dan Webb (EDIS)
The Dairy Business Analysis Program (DBAP) is a cooperative effort of the Universities of Florida and Georgia, Southeast Milk Inc., and Southeast Dairy Herd Improvement Association, Inc. (DHIA). This project annually surveys participating dairy farms about their revenues, expenses, and investments.  This document is DS179, one of a series of the Animal Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 11, 2005.